Investigating Differences Between Drugs Used in the Australian Night-Time Economy: Demographics, Substance Use, and Harm. (2nd January 2017) - Pennay, Amy; Jenkinson, Rebecca; Quinn, Brendan; Droste, Nicolas Tom; Peacock, Amy; Lubman, Daniel Ian; Miller, Peter G.
ABSTRACT: Background: Understanding the characteristics of drug users in the night-time economy (NTE), and whether particular drugs are associated with risky practices and experience of harm, is necessary to inform targeted policy responses in this context. Objectives: To investigate the correlates of drugs used in the Australian NTE relating to demographics, alcohol use, and experience of harm. Methods: Patrons were interviewed in the NTE of five Australian cities in 2012–2013 ( n = 7, 028; 61.9% male, median age 22 years). A custom designed survey gathered demographic data, alcohol, and substance use on the current night, and experience of harm in/around licensed venues in the past 3 months. Multivariate logistic regression analyses examined the correlates of drug use. Results: Ecstasy was most commonly reported (4.0%), followed by cannabis (2.9%), methamphetamine (2.6%), and cocaine (1.6%). Ecstasy users were more likely to be younger and report energy drink consumption. Cannabis users were more likely to be male, and to have been involved in intoxication-related accidents/injuries and sexual aggression in/around licensed venues in the past 3 months. Methamphetamine users were more likely to have been interviewed later, and to have engaged in pre-drinking. Cocaine users were more likely to be male, aged 21 years or more, have a blood alcohol concentration of greater than 0.10%, and to have been involved in intoxication-related accidents/injuries in the past three months. Conclusions/Importance: We identified significant differences between types of drug users and the harms they experience, underscoring the need to develop innovative harm reduction policies in the NTE rather than blanket population-based approaches.